1989
DOI: 10.1177/0741088389006002004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Writing on Learning from Expository Text

Abstract: While writing researchers and theorists have claimed that composing fosters learning, we need a more rigorous conceptualization of the effects of various writing tasks on learning. This study attempted to refine and extend present knowledge of the interrelationship of writing and learning by examining the effects of various writing tasks (notetaking, answering study questions, and essay writing) on learning using recall of specific text elements and recall of the theme or gist of expository writing. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…One finding of Langer's and Applebee's three studies that has important implications for teachers of environmental science is that different kinds of writing tasks result in different kinds of cognitive operations, and hence different kinds of learning. (This conclusion has been replicated in other studies; see, for example : Durst 1987, Newell and Winograd 1989, Tierney and others 1989 For example, notetaking, answering comprehension questions, and summarizing may be the tasks of choice when the instructor's purpose is to review a general body of information with the goal of reinforcing students' recognition and recall skills. However, analytic writing will be the task of choice when the emphasis is upon concepts and relationships in contexts, where these relationships are more important than memory for a large body of facts.…”
Section: Using Written and Verbal Dialogue As Modes Of Thinking And Lmentioning
confidence: 52%
“…One finding of Langer's and Applebee's three studies that has important implications for teachers of environmental science is that different kinds of writing tasks result in different kinds of cognitive operations, and hence different kinds of learning. (This conclusion has been replicated in other studies; see, for example : Durst 1987, Newell and Winograd 1989, Tierney and others 1989 For example, notetaking, answering comprehension questions, and summarizing may be the tasks of choice when the instructor's purpose is to review a general body of information with the goal of reinforcing students' recognition and recall skills. However, analytic writing will be the task of choice when the emphasis is upon concepts and relationships in contexts, where these relationships are more important than memory for a large body of facts.…”
Section: Using Written and Verbal Dialogue As Modes Of Thinking And Lmentioning
confidence: 52%
“…Furthermore, as Jones (1991) documents and recommends, if these topics were to be used as a context for writing, both knowledge and interest may be enhanced, leading to the development of more complex and creative ideas (Konopek et al, 1991). A higher level of content integration (Newell & Winograd, 1989) may also be the result.…”
Section: Discussionmentioning
confidence: 99%
“…The results here suggest that writing prompts might be useful, at least for students lacking experience in informal and personal writing in science. Based on views offered by Soter (1987), Ruth & Murphy (1988), Newell & Winograd (1989), White (1989) and Konopek et al (1991), it is likely that with the appropriate writing prompts, a writing activity for students can be less difficult and confusing, motivating them to develop more complex and creative science-related ideas, and encouraging the expression of a higher level of content integration.…”
Section: Discussionmentioning
confidence: 99%
“…He found that students who wrote analytical essays learned more passage-specific content than those engaged in more restricted writing tasks that invited students to review information in a given text. A follow-up study based on these data (G. E. Newell & Winograd, 1989) showed that students who wrote analysis papers were more sensitive to structural importance-that is, to how important ideas in a prose passage related to one another-than those who answered study questions or took notes. There was also a significant effect for task on recall favoring those who wrote essays; for these students, an understanding of structural importance apparently "facilitated their ability to recall the gist" (p. 207).…”
Section: Literacy As Learning Literacy As Engagementmentioning
confidence: 99%